PROBLEM SAINS MODERN DI BARAT: PENTINGNYA PEMIKIR ISLAM KONSTRUKTIF – POSITIF - M. Abzar D; Syahrial Syahrial (Sulesana: Jurnal Wawasan Keislaman, 2021)
A fact, the modern Western world has successfully demonstrated its progress in science and technology. Various kinds of technology have been found to have a positive impact on the world. Such as the ease of transportation, communication, industry and security. However, in it still tucked and attached negative influence that become a global crisis. Such as environmental crises, poverty, morality, economic injustice, religious awareness including the declining quality of health. Science and technology which originally wanted to solve the world’s problems, and this became a setback in world civilization. This paper examines how problematic the modern scientific paradigm is in the West and the role of the Islamic world. The contributions of earlier Islamic scientists and thinkers have become evidence of how Islam pays great attention to science. through efforts to create Islamic thinkers who think constructively and positively can help solve the problem of modern science.